PERSEPSI MASYARAKAT TENTANG AKAN DI KONVERSIKANNYA BANK KONVENSIONAL KE BANK SYARIAH DI ACEH STUDI KASUS DI KOTA LANGSA - Kismawadi, Early Ridho; Al Muddatstsir, Uun Dwi (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2018)
This study aims to determine the public perception in the city of Langsa about Aceh Qanun related to Aceh provincial Qanun No. 8 0f 2014 concerning in the principles of Islamic Law and Qanun No. 8 of 2016 concerning the Halal Product Guarantee System which requires banks to operate in Aceh to be based on sharia principles. The method used in the study is qualitative descriptive. The results of this study the community is very supportive for the enactment of these regulations, but the public hopes that islamic banks operating in the province of Aceh must provide the same facilities as conventional banks which are currently very good compared to islamic banks in terms of facilities owned.